2018
DOI: 10.12659/msm.906176
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of GLI1 and Related Signaling Pathways in Chemosensitivity of Gastric Cancer

Abstract: BackgroundThis study assessed the prognostic value of GLI1 in gastric cancer and analyzed the possible GLI1-related signaling network in chemosensitivity.Material/MethodsBioinformatic data mining was performed by using data in the TCGA-Stomach Cancer (TCGA-STAD) and the Kaplan-Meier plotter. GLI1 co-expressed genes in TCGA-STAD were subjected to KEGG pathway analysis. The genes enriched in the KEGG pathways were further subjected to Protein-Protein Interaction (PPI) analysis.ResultsIn TCGA-STAD, high GLI1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…KM plotter is a widely used database containing gene expression data and survival information. 17 Until now, a number of genes, such as ALDH1, GLI1, ITIH5, CK2, RAI14 , and GREB1 , have been identified and validated by KM plotter in lung, 16 , 28 , 52 , 53 breast, 19 28 , 54 gastric, 55 , 56 and ovarian cancers. 28 , 57 , 58 Using KM plotter, we determined the prognostic value of individual GPx mRNA in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…KM plotter is a widely used database containing gene expression data and survival information. 17 Until now, a number of genes, such as ALDH1, GLI1, ITIH5, CK2, RAI14 , and GREB1 , have been identified and validated by KM plotter in lung, 16 , 28 , 52 , 53 breast, 19 28 , 54 gastric, 55 , 56 and ovarian cancers. 28 , 57 , 58 Using KM plotter, we determined the prognostic value of individual GPx mRNA in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…A bioinformatics analysis showed that the DEGs of EC compared with normal tissues are mainly enriched in the PI3K-Akt signaling pathway Yu-Jing et al, 2020). Moreover, GLI1 co-expressed and DEGs between tumor samples and normal tissues were both largely enriched in the PI3K-Akt pathway in STAD (Yu et al, 2018;Li et al, 2019). In PAAD, 4-miRNA as independent prognostic factor was found to be related to the PI3K-Akt signaling pathway (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…These altered DEGs may be co-expressed in different types of cancer and participate in tumorigenesis, such as that of chronic myeloid leukemia and small cell lung cancer, according to KEGG pathway analysis. In the multi-stage development of cancer, the imbalance of the equilibrium steady state of the activity of signaling pathways responsible for cell cycle regulation and division will lead to the inhibition of apoptosis and the enhancement of cell proliferation (31). Tight junctions are protein structures that control the transport of water, ions and macromolecules across cell layers (32).…”
Section: Discussionmentioning
confidence: 99%